B2B Brand Management - Kotler, Philip; Pfoertsch, Waldemar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
As products become increasingly similar, companies are turning to branding as a way to create a preference for their offerings. Branding has been the essential factor in the success of well-known consumer goods such as Coca Cola, McDonald's, Kodak, and Mercedes. Now it is time for more industrial companies to start using branding in a sophisticated way. Some industrial companies have led the way... Caterpillar, DuPont, Siemens, GE. But industrial companies must understand that branding goes far beyond building names for a set of offerings. Branding is about promising that the company's offering will create and deliver a certain level of performance. The promise behind the brand becomes the motivating force for all the activities of the company and its partners. Our book is one of the first to probe deeply into the art and science of branding industrial products. We provide the concepts, the theory, and dozens of cases illustrating the successful branding of industrial goods.
Being Known or Being One of Many -- To Brand or Not to Brand -- B2B Branding Dimensions -- Acceleration Through Branding -- Success Stories of B2B Branding -- Beware of Branding Pitfalls -- Future Perspective.
Keywords: Marketing; Management; Marketing; Management